Metal-free Lewis pair catalyst synergy for fully alternating copolymerization of norbornene anhydride and epoxides: Biocompatible tests for derived polymers. (June 2019) - Kummari, Anjaneyulu; Pappuru, Sreenath; Gupta, Piyush Kumar; Chakraborty, Debashis; Verma, Rama Shanker
Graphical abstract: Metal-free Lewis pair as a cooperative catalyst for fully alternating copolymerization of norbornene anhydride and epoxides. Highlights: The catalytic activity of B(C2 H5 )3 /DMAP system for norbornene anhydride-epoxide ring-opening copolymerization is described. The ROCOP studies have been carried out in sufficient details which include studies on catalyst reactivity and the determination of the polymerization pathway using synthesis. The characterization of all synthesized polymers have been done in a detailed, systematic and in a rigorous manner. The polyesters are biocompatible as tested with human embryonic kidney cells (HEK-293) showing more than 80% cell viability in 72 h. Abstract: Synthesis of high molecular weight alternating copolymers from epoxides and norbornene anhydride via metal-free catalyst remains a challenge in aliphatic biodegradable polyester synthesis. Metal-free Lewis pair catalyst system, consisting of Lewis acid B(C2 H5 )3 (triethylborane) and a Lewis base DMAP (4-dimethylaminopyridine); TBD (1, 5, 7-triazabicyclo[4.4.0]dec-5-ene) and DBU (1, 8 diazabicyclo[5.4.0]undec-7-ene) as a cooperative catalyst system for fully alternating polyesters synthesis is described here. By using these simple systems we have obtained, high molecular weight ( M n = 2–31.5 kDa) polyesters with narrow molecular weight distributions (MWD's = 1.948–1.069) via ring-opening alternating copolymerisation (ROAC) of various epoxides ( e.g. CHO, cyclohexene oxide; PO, propylene oxide; t BGE, tert -butyl glycidyl ether and PGE, phenyl glycidyl ether) with cis -5 norbornene-endo 2, 3 dicarboxylic anhydride (NB). Furthermore, we demonstrated that these polyesters are biocompatible in nature when tested on human embryonic kidney cells (HEK-293) showing more than 80% cell viability in 72 h and can be used for different biological applications such as drug delivery, tissue engineering or anti-microbial polymeric coatings on biomedical devices. The use of these green functional polyesters for biological studies was realized for the ﬁrst time by a metal-free Lewis pair approach.